Management of advanced gastric cancer. (April 2012) - Price, Timothy J; Shapiro, Jeremy D; Segelov, Eva; Karapetis, Christos S; Pavlakis, Nick; Van Cutsem, Eric; Shah, Manish A; Kang, Yoon-Koo; Tebbutt, Niall C
The management of advanced gastric cancer has only evolved a little over the last 15 years: platinum and fluoropyrimidine chemotherapy remains the backbone of therapy with ongoing debate as to the benefit of triplet therapy with either an anthracycline or taxane. Recently published trials of biological agents, in particular those targeting the Her2 receptor, have provided some signs of improvement. This article summarizes the relevant literature, discusses the role of these agents, as well as geographical variations in use, and provides recommendations regarding both 'standard chemotherapy'' and the role of biological agents in advanced gastric cancer. Given the relative lack of progress for gastric cancer over the last 15 years, the focus for the next 5 years should be on an improved understanding of the molecular basis of gastric cancer, thus allowing rational integration of new molecular agents.